2009
DOI: 10.3758/app.71.8.1725
|View full text |Cite
|
Sign up to set email alerts
|

The "beam of darkness": Spreading of the attentional blink within and between objects

Abstract: When two targets (T1 and T2) are inserted into a rapid serial visual presentation (RSVP) stream of nontargets, observers are impaired at identifying T2 when it is presented within half a second after T1. This transient drop in performance, or attentional blink (AB), has been attributed to a temporary unavailability of task-critical processing resources. In the present study, we investigated how object-based attention modulates the AB, by presenting four synchronized RSVP streams in the corners of two rectangul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…The finding of a same-object benefit for identical T1 and T2 stimuli in Experiment 2 is also consistent with Raymond (2003; see also Conci & Müller, 2009). Our results mirror these previous findings and further show that repeated perceptual objects (Experiment 2), rather than repeated response-defining features (Experiment 1), lead to a reduction of the AB.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The finding of a same-object benefit for identical T1 and T2 stimuli in Experiment 2 is also consistent with Raymond (2003; see also Conci & Müller, 2009). Our results mirror these previous findings and further show that repeated perceptual objects (Experiment 2), rather than repeated response-defining features (Experiment 1), lead to a reduction of the AB.…”
Section: Discussionsupporting
confidence: 78%
“…The results from Experiment 1 failed to show spared lag-1 performance; rather, the AB was particularly pronounced at lag 1. This may have resulted from the task switch between two targets (from a local-object direction discrimination task to a global-shape “counting” task) and from the relatively long T1-T2 lag (120 ms; see also Conci & Müller, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…is frequently reported for horizontal objects, whereas a same object cost (i.e., slower RTs to invalid locations on a cued object versus a non-cued object) has been reported for vertical objects (Al-Janabi & Greenberg, 2016;Conci & Müller, 2009;Harrison & Feldman, 2009;Hein, Blaschke, & Rolke, 2016;Pilz, Roggeveen, Creighton, Bennet, & Sekular, 2012). Our work previously investigated this dissociation by comparing the reallocation of object-based attention across the horizontal versus vertical meridian using an 'L'-shaped object (Barnas & Greenberg, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have suggested that object orientation can affect the sign of object-based selection effects (Conci & Müller, 2009;de-Wit, Kentridge, & Milner, 2009;Harrison & Feldman, 2009;Pilz et al, 2012). Pilz et al, for example, asked participants to identify a target in the double-rectangle cueing paradigm (Exp.…”
mentioning
confidence: 99%